Improving Accouting Policies in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article reveals necessity and significance of accounting policy in Uzbekistan. In addition, the article analyzes requirements for the development of the accounting policy and the factors influencing it, as well as the methodological foundations for the formation of accounting policy in reliance upon the international financial reporting standards. Furthermore, the article presents the considerations and opinions of economists on accounting policy, issues of improvement of the statutory acts related to accounting policy.